Idiopathic hypereosinophilic syndrome with unusual presentation : two case reports and review of literature - Suria Abdul Aziz,; Hafizah H,; Nurasyikin Yusof,; Azlin Ithnin,; Yousuf R,; Azma RZ,; Hamidah NH, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Idiopathic hypereosinophilic syndrome (HES) is an uncommon disorder which usually presents with prolonged and significant primary eosinophilia with end-organ dysfunction. Damaging proteins released by the eosinophilic granules are responsible for the tissues and organ system damage. Here we report two cases of idiopathic HES. Both the patients were young lady presented with high grade fever and concomitant symptoms. Laboratory findings showed leucocytosis with predominant neutrophilia and marked eosinophilia. A diagnosis of idiopathic HES was made after excluding secondary causes of eosinophilia. However, the first patient was complicated with multiple venous thrombosis and intravenous heparin was started which was later changed to subcutaneous low molecular weight heparin (LMWH). The patient developed pleural effusion and consolidation. Intravenous Tazoscin, tablet Prednisolone and tablet Hydroxyurea was started and the patient responded well. Despite treatment, two weeks later, suddenly the patient collapsed and unfortunately succumbed. On the other hand, the second patient was complicated with fever, thrombocytopenia, haemolytic anaemia, acute renal failure and neurological deficit which were part and parcel of thrombotic thrombocytopenic purpura (TTP). Plasma exchange was commenced and patient’s condition had slowly improved. Nevertheless, the hypoxia which she sustained during the multiple episodes of fits had resulted in permanent brain injury and thus requiring a tracheostomy for prolonged ventilatory support. Currently, there is no cure for HES. The main aim of treatment is to minimise the tissue damage caused by the hypereosinophilia. Early diagnosis and intervention are therefore crucial in preventing the spread of the disease and the end-organ damage.